Customer value in lean product development: Conceptual model for incremental innovations. Issue 3 (6th October 2019) - Santos, Ana Carolina Oliveira; da Silva, Carlos Eduardo Sanches; Braga, Rodrigo Aparecido da Silva; Corrêa, João Éderson; de Almeida, Fabricio Alves
Abstract: As the lean product development (LPD) process is responsible for maximizing the value/waste relation by encouraging different types of innovation, it needs a clear understanding of end customer value. Moreover, lean systems engineering is related to the application of lean thinking (LT) in systems engineering to improve the delivery of value to all stakeholders of the system. Then, faced with this scenario, this research aims to propose a value‐adding conceptual model for incremental product innovations in LPD. A systematic review of the literature from the LT perspective was performed and the conceptions of value were identified and then analyzed and contrasted with the concepts and characteristics of the areas of product development, marketing, and consumer psychology, which made possible the proposition of a conceptual model. The results show that customer value is multidimensional, and it was possible to identify the importance and the need for prioritization of certain dimensions of value for specific markets and customers. The conceptual model named VA2I presented in this study is generic and can be adapted and applied in any type of organization.